ASESMEN OTENTIK: IMPLEMENTASI DAN PERMASALAHANNYA DALAM PEMBELAJARAN BAHASA INGGRIS DI SEKOLAH MENENGAH - Muhammad Zaim (International Conference on Languages and Arts, 2013)
The aims of this research are to find out the teachers’ knowledge about authentic assessment, how to arrange the instruments of authentic assessment, how to implement authentic assessment, the consideration of authentic assessment in deciding final mark of the students, the problems faced by the teachers. The subjects of the research are 10 teachers and 56 students of grade VII and VIII of Junior High School A and B Padang. The data were collected through questionaire, interview, and document analysis. The data were analysed descriptively. The findings of the research are (1) the teachers’ knowledge about authentic assessment is good enough to implement authentic assessment based on the standard of authentic assessment; (2) teachers are able to arrange the instruments of authentic assessment, especially on speaking and writing, but because there were various kind of text to be assessed, teachers’ knowledge have to be increased; (3) the implementation of authentic assessment is not good enough in the process of learning, (4) teachers still need training and guidance book to implement authentic assessment in learning process.